Help button for elderly people on the Arduino platform (2018)
The design and implementation of a system capable of providing elderly people with a fast track to ask for help, remotely, to the person in charge of their care, using the cellular network is reported t. The main functionality is a help button, through which the person in charge of the elderly care will receive a text message when the elder presses the button. Recognizing the little connection between the people of this age group with cellular technology, defining the number to which the messages will be sent (and writing them) is not their task. The system has other features of great value, as a group of automatic alarms, also operating via SMS, generated by a group of sensors included in the system, which facilitates remote decision making from caregivers.